Interspinous Process Decompression: Expanding Treatment Options for Lumbar Spinal Stenosis. (13th October 2016) - Nunley, Pierce D.; Shamie, A. Nick; Blumenthal, Scott L.; Orndorff, Douglas; Block, Jon E.; Geisler, Fred H.
Abstract : Interspinous process decompression is a minimally invasive implantation procedure employing a stand-alone interspinous spacer that functions as an extension blocker to prevent compression of neural elements without direct surgical removal of tissue adjacent to the nerves. The Superion® spacer is the only FDA approved stand-alone device available in the US. It is also the only spacer approved by the CMS to be implanted in an ambulatory surgery center. We computed the within-group effect sizes from the Superion IDE trial and compared them to results extrapolated from two randomized trials of decompressive laminectomy. For the ODI, effect sizes were all very large (>1.0) for Superion and laminectomy at 2, 3, and 4 years. For ZCQ, the 2-year Superion symptom severity (1.26) and physical function (1.29) domains were very large ; laminectomy effect sizes were very large (1.07) for symptom severity and large for physical function (0.80). Current projections indicate a marked increase in the number of patients with spinal stenosis. Consequently, there remains a keen interest in minimally invasive treatment options that delay or obviate the need for invasive surgical procedures, such as decompressive laminectomy or fusion. Stand-alone interspinous spacers may fill a currently unmet treatment gap in the continuum of care and help to reduce the burden of this chronic degenerative condition on the health care system.